Comparison Model Hargreaves, Annandale and New Model for Estimation of Solar Radiation in Perlis, Malaysia - Suwarno Suwarno; Rohana Rohana (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Sunlight is a potential source of electrical energy in the universe. Utilization of solar radiation is not optimal to be a source of electricity generation. Before harnessed solar radiation in order to know in advance the estimated potential energy. Modelling estimates of solar radiation in three models: models Hargreaves, Annandale and the proposed new model. The new model proposed solar radiation estimates based on models Hargreaves and Annandale. Some models for estimating solar radiation is discussed in this paper which aims to determine the potential of solar radiation into electrical energy potential. A new model is proposed to estimate solar radiation. Comparison of the three models are estimated using statistical analysis e (%), CRM, and RMSE is obtained that the proposed new model is better, when compared to other models.